BCG cell wall skeleton augments the immunogenicity of dengue nanoparticle vaccines by promoting dendritic cell activation - Jitra Limthongkul; Saradee Warit; Panya Sunintaboon; Sukathida Ubol; Tuksin Jearanaiwitayakul (PLoS ONE, 2025)
Bacillus Calmette-Guérin cell wall skeleton (BCG-CWS) has been shown to enhance vaccine effectiveness and antitumor immunity. In our previous study, we reported that co-administration of BCG-CWS with the encapsidated dengue antigens, UV-inactivated DENV2 and DENV2 NS1, synergistically induced DENV-specific adaptive immune responses in mice. As dendritic cells (DCs) are key immune players that mediate innate and adaptive immunity, we, here, asked how well the response of DCs to this adjuvant aligns with the immune responses elicited in vivo . The responses of primary monocyte-derived DCs to BCG-CWS-adjuvanted encapsidated dengue immunogens compared with the unadjuvanted vaccine were investigated. DCs stimulated by BCG-CWS and the dengue nanoparticle vaccine exhibited a superior response. This response correlated well with the stronger immune response observed in mice. This was evidenced by the marked elevation in expression levels of DC activation markers, such as CD80, CD83, CD86, and HLA-DR, and various innate immune cytokines. Additionally, this adjuvant markedly elevated the expression levels of miRNAs related to DC function, such as miR-146a, miR-147, miR-223, and miR-155. These immune components could suppress DENV2 multiplication in bystander skin cells. BCG-CWS exerted an adjuvant effect on DC responses by enhancing antigen-processing activity and activating several innate immune cytokines and immune-related miRNAs.